The warmth of other suns : the epic story of America's great migration - Wilkerson, Isabel (Random House, 2010)
In this epic, beautifully written masterwork, Pulitzer Prize-winning author Isabel Wilkerson chronicles one of the great untold stories of American history: the decades-long migration of black citizens who fled the South for northern and western cities, in search of a better life. From 1915 to 1970, this exodus of almost six million people changed the face of America.